Is job sharing worthwhile? : a cost-benefit analysis in UK universities - Harris, Geoff [Verfasser] (My University, 1997)
"Around 60 per cent of Uk universities practice job sharing. This article is based on a survey of Personnel Directors in UK universities concerning their perceptions of job sharing. These responses were then used to carry out a cost benefit evaluation of job sharing from the universities perspective. If productivity of workers in the shared job rose by a little as 0.35 per cent - one third of one per cent - the estimated increase in Personnell Section costs would be covered. If there was a 5 per cent increase in productivity, the ratio of benefits to costs would be 14.3 to 1. Universities also save as a result of greater retention of staff, and there are also important benefits to society, particularly less overall stress and reduced unemployment levels." (author's abstract) ((en)) Der Artikel berichtet über Ergebnisse einer Befragung bei Personalabteilungsleitern britischer Universitäten zum Thema Job sharing. Es wurde eine Kosten-Nutzen-Analyse durchgeführt, um Auswirkungen auf Produktivität, Kostenersparnis und Nutzen für die Gesellschaft zu ermitteln. (IAB)
Keywords: G 1.2.2.3 Beschäftigungsformen; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 3 Institutionen; I 2.2.1 Westeuropa; Arbeitsplatzteilung; Hochschulpersonal; Kosten-Nutzen-Analyse; Arbeitsproduktivität; Universität; Großbritannien